The Ritual of Capitalization - Blair Fix (Real-World Economics Review, 2021)
For more than a century, political economists have sought to understand the nature of capital. The prevailing wisdom is that there must be something `real' – some productive capacity – that underpins capitalized values. This thinking, I argue, is a mistake. Building on Jonathan Nitzan and Shimshon Bichler's theory of capital as power, I argue that capitalization is an ideology. It is a quantitative ritual for converting earnings into present value. Although the ritual is arbitrary, it gives rise to astonishing empirical regularities, reviewed here.
Keywords: P16; P26; P48; G; P; G1; E44; 330; capitalization; discounting; power; stock market